Faktor-faktor risiko katarak: kajian di kalangan pesakit katarak di Wad oftalmologi Hospital Kuala Lumpur - Ana Daliela M.; Azmi B.; Hazlina Y.; Khor J.G.; Mimi Marina M.I.; Mohd. Zaidi S.; Govindarajanthran N.; Zahriah J.; Zalifa Z.A. (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 1998)
A case-control study was conducted to study the risk factors for cataract among cataract patients in the ophthalmology wards of Kuala Lumpur Hospital from 2-16th October 1995. The risk factor studied were age, ethnicity, diabetes mellitus,hypertension, smoking habits and obesity. Sixty-six cataract cases were interviewed. All cases chosen have had cataract operation done or are waiting to be operated on. Controls were non-cataract patients from the medical wards.Cases and control were matched by sex. Result show that the significant risk factors for cataract are aging (Odds Ratio of 9.4, 95% confidence interval 3.3-28.1), diabetes mellitus (Odds Ratio of 3.0, 95% confidence interval 1.3-7.1) and smoking (Odds Ratio of 2.6, 95% confidence interval 1.0-6.7). Other factors such as ethnicity, hypertension and obesity were not statistically significant in the analysis.